Pengaruh Kepemimpinan Instruksional Kepala Sekolah Dan Iklim Sekolah Terhadap Kualitas Pembelajaran di SD Negeri Sekecamatan Suruh - Inayah, Inayah; Nurkolis, Nurkolis; Wuryandini, Endang (Jayapangus Press, 2025)
Learning is said to be of quality if students are actively involved in the learning process by showing a great enthusiasm for learning and self-confidence. The purpose of this study was to determine the magnitude of the influence of the principal's instructional leadership and school climate together on the quality of learning. The research approach used was quantitative. This type of research uses correlation research. The population of this study was 281 teachers and the research sample was 165 teachers. Data collection was carried out using a questionnaire. The data analysis techniques used in this study were descriptive data analysis, prerequisite tests including normality tests, multicollinearity tests, heteroscedasticity tests, linearity tests and hypothesis tests including simple and multiple linear regression. The results of the study showed that: (1) the correlation of the principal's instructional leadership on the quality of learning was 0.677. The influence of the principal's instructional leadership had a significant effect on the learning quality variable by 65.8%. (2) The correlation of school climate on the quality of learning was 0.672. The influence of school climate had a significant effect on the learning quality variable by 65.1%. (3) The significant influence of the principal's instructional leadership and school climate on the quality of learning with the equation Ŷ = 8.390 + 0.612 X1 + 0.488 X2. Then the correlation coefficient value r is 0.759. The result of the coefficient of determination of the influence of variables X1 and X2 on Y is 77.5%.